Structural analysis and antioxidant activity of the glycoside from Imperial Chrysanthemum. Issue 9 (15th May 2018) - Zhu, Zhen-Yuan; Pan, Li-Chao; Yun-Tang,; Zhang, Yong-min
Graphical abstract: Highlights: A new glycoside was extracted from Imperial Chrysanthemum . The glycoside showed excellent antioxidant activity. The structure was deduced by NMR, HPLC-MS and FT-IR. The glycoside showed good thermal stability. Abstract: A new glycoside, named as CG-1, was separated from Imperial Chrysanthemum with silica gel column chromatography. The purity was detected by TLC and HPLC. The crystal shape of CG-1 was consisting of a quadrangular and two rectangular pyramids. The analysis of DSC and TGA showed that the melting point of CG-1 crystal was 150.22 °C and had good thermal stability. The monosaccharide conformation analysis showed that it was d -glucose. The structure characteristics were compared by FT-IR, NMR spectroscopy and LC-MS and a molecular structure has been deduced which consistent with spectroscopic results. In vitro antioxidant results suggested that the glycoside extracted from Imperial Chrysanthemum could be effectively employed as natural antioxidant in health or functional food. This work is of significance to keep the antioxidant activity in the processing and application of Imperial Chrysanthemum .